Review of the Chinese Stomis, with description of nine new taxa and a new key (Carabidae: Pterostichini) - Sciaky, Riccardo (Zootaxa, 2024)
In this work the Chinese species of the genus Stomis Clairville, 1806 are reviewed and divided into five species-groups. Nine new taxa are described: S. vignai ssp. maior ssp. nov. is a subspecies of S. vignai from eastern Sichuan and western Shaanxi with large size and very transverse pronotum; S. vignai ssp. megacephalus ssp. nov. is a subspecies of S. vignai from Hubei with large size, very large head and short mandibles; S. exilis ssp. pauli ssp. nov. is a subspecies from Henan, the easternmost taxon of the genus, characterized by elongate body and rounded elytra; S. wrasei sp. nov. is a species from Sichuan of the S. chinensis-group related to S. gigas Sciaky, 1998, but with slenderer and flatter elytra and deeper and more markedly punctate striae; S. davidi sp. nov. is a species from Sichuan of the S. chinensis-group related to S. titanus Sciaky, 1998, but different in the narrower and more convex body, stronger greenish hue, smaller pronotum with more abrupt constriction before base, striae more superficial and less evidently punctate; S. bousqueti sp. nov., from Sichuan, is a species of the S. robustus-group previously confused with S. chinensis and as such mentioned in previous works; it is the smallest species in the S. chinensis-group and has square shoulders and well-developed eyes; S. magrinii sp. nov. is a species from Shaanxi and Sichuan of the S. robustus-group, related to S. bousqueti, but different in the larger size and more rounded elytra; S. dilaticollis sp. nov. is a species from Yunnan of the S. robustus-group related to S. robustus, but smaller and with pronotum more markedly constricted towards base; S. jani sp. nov. is a species from Sichuan of the S. robustus-group related to S. dilaticollis, but larger, more evidently depressed and with proportionally longer elytra. Many new distributional data are given for many of the known species and some systematic and synonymic notes on other Chinese species of the genus are given, too. The new nomenclatural acts here proposed are: Stomis cavazzutii Lassalle, 2003 = S. vignai Sciaky, 1998 syn. nov.; Stomis taibashanensis Lassalle, 2003 = S. vignai ssp. taibashanensis Lassalle, 2003 stat. nov.; Stomis fallettii Facchini, 2003 = S. vignai ssp. taibashanensis Lassalle, 2003 syn. nov.; Stomis brivioi Sciaky, 1998 = S. exilis ssp. brivioi Sciaky, 1998 stat. nov.; Stomis brivioi ssp. taoyuanensis Lassalle, 2003 = S. exilis ssp. brivioi Sciaky, 1998 syn. nov.; Stomis ludmilae Dvořák, 2001 = Stomis romani Dvořák, 2001 syn. nov.; Stomis jelineki Lassalle, 2003 = Stomis romani Dvořák, 2001 syn. nov.; Stomis benesi Dvořák, 2006 = Stomis romani Dvořák, 2001 syn. nov.; Stomis elongatus Tian & Pan, 2004 = Stomis schoenmanni Sciaky, 1998 syn. nov. Eventually, a new key and a summarized list of the Chinese species of this genus is proposed.